Pengaruh Pertanian Peduli Maslahah Terhadap Tingkat Kesejahteraan Petani Dan Komunitas Lokal Di Desa Tea Malala Kecamatan Ulaweng Kabupaten Bone - Sahrani, Ananda Diva; Darwis, Rahma Hidayati; Safar, Jumriani (Bisnis-Net, 2025)
This study aims to determine the partial effect of the Maslahah-oriented agriculture variable on the welfare level of farmers and the local community in Tea Malala Village, Ulaweng District, Bone Regency. This research uses a quantitative approach, with the sample selected through simple random sampling, totaling 92 respondents. Data collection was conducted using a questionnaire, while data analysis employed simple linear regression analysis. Data processing in this study was conducted using SPSS 27 software. The results of the study indicate a positive and significant effect of Maslahah-oriented agriculture on the welfare level of farmers and the local community in Tea Malala Village, as shown by the t-value of 11.136, which is greater than the t-table value of 1.987. The coefficient of determination (R²) analysis shows a value of 0.579, indicating that Maslahah-oriented agriculture contributes 57.9% to the welfare of farmers and the local community, while the remaining 42.1% is influenced by other variables not included in this study..